PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) SEBAGAI UPAYA PENINGKATKAN HASIL BELAJAR SISWA PADA MATA DIKLAT AKUNTANSI KELAS XI DI SMK NEGERI 1 BOJONEGORO - RISA RIA ROSIDA (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
NHT (Numbered Heads Together) is very effective in improving student learning outcomes as NHT is a type of cooperative learning that is designed to influence the patterns of student interaction and as an alternative to the traditional classroom structure. In this type of structural approach NHT (Numbered Head Together) requires the student to work and interact with each other in small groups are more characterized by the award of cooperative rather than individual pengharaan. In this model the student occupies a dominant position in the learning process and the cooperation in the group with its main characteristic the numbering so that all students strive to understand each of the material being taught and are responsible for the number of their members. With the selection of this model of learning that occurs can be more meaningful and give a strong impression to the students. Keyword: Type Nubered Heads Together, Learning Outcomes